Pengaruh Literasi Keuangan , Modal Minimum, Persepsi Return dan Risiko terhadap Minat Berinvestasi Mahasiswa - Novendra Wahyu Wardana; Dhiah Fitrayati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Students are one of the targets of the Indonesia Stock Exchange in increasing young investors. However, based on the survey results, it is known that of 8 students in the economic education study program, there is only one student who invests. This study aimed to estimate the effect of financial literacy, minimum capital, perceived return, and risk on investment interest. The method used in this study is a quantitative method. The economic education study program FEB UNESA is the population in this study 120 people. After that, samples were taken using the Slovin formula for as many as 92 people. Furthermore, the research sample was taken using a probability sampling technique with a proportionate stratified random sampling. Data accumulation was clear by using a questionnaire. Before the questionnaires were dispart to all respondents, the validity and reliability tests of the research instruments were first tested. Data analysis using multiple linear regression test method. From the results of data analysis, it was found that financial literacy and minimum capital did not affect students' investment interest, while the perception of return and risk significantly affected students' investment interest in the economic education study program FEB UNESA. Keywords: Financial literacy, Minimum Capital, Perceived Return and Risk